2000
DOI: 10.1086/301483
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of Disk Evolution and Planet Formation: [ITAL]HST[/ITAL], Adaptive Optics, and [ITAL]ISO[/ITAL] Observations of Weak-Line and Post–T Tauri Stars

Abstract: We present high-spatial resolution HST and ground-based adaptive optics observations, and highsensitivity ISO (ISOCAM & ISOPHOT) observations of a sample of X-ray selected weak-line (WTTS) and post (PTTS) T Tauri stars located in the nearby Chamaeleon T and Scorpius-Centaurus OB associations. HST/NICMOS and adaptive optics observations aimed at identifying substellar companions (young brown dwarfs) at separations ≥ 30 A.U. from the primary stars. No such objects were found within 300 A.U. of any of the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 42 publications
7
88
0
Order By: Relevance
“…We summarize here their properties, as the binarity has to be considered to correct photometric distances and temperatures; binarity is also relevant for a proper interpretation of the age indicators. Three close binaries were previously known: HIP 108422 (Chauvin et al 2003, physical association confirmed by our NaCo observations), TYC 7835-2569-1 (Brandner et al 1996), and TYC 6786-0811-1 (Köhler et al 2000). Three of the newly discovered companions are proposed members of the AB Dor moving group (MG) and one belongs to the Cha group.…”
Section: Visual Binariessupporting
confidence: 56%
See 1 more Smart Citation
“…We summarize here their properties, as the binarity has to be considered to correct photometric distances and temperatures; binarity is also relevant for a proper interpretation of the age indicators. Three close binaries were previously known: HIP 108422 (Chauvin et al 2003, physical association confirmed by our NaCo observations), TYC 7835-2569-1 (Brandner et al 1996), and TYC 6786-0811-1 (Köhler et al 2000). Three of the newly discovered companions are proposed members of the AB Dor moving group (MG) and one belongs to the Cha group.…”
Section: Visual Binariessupporting
confidence: 56%
“…However, we can not conclusively demonstrate this without a measurement of the binary's orbital period. TYC 7835-2569-1 = HD 137059 (ASAS 152517−3845.4;1SWASP+J152516.99-384526.0) Close visual binary (1.05 arcsec separation, ΔV = 0.3 mag, ΔH = 0.1 mag) first discovered by Brandner et al (1996) and confirmed by NaCo-LP data. The star was found to be SB2 from CORAVEL spectra.…”
Section: Hip 36948 = Hd 61005mentioning
confidence: 74%
“…5.4 and 5.5) of our sample, among which five appear as possible members of young stellar kinematical groups in the solar neighbourhood. Brandner et al (1996) have pointed out that ROSAT unresolved binaries are X-ray sources statistically brighter than single stars. Thus, X-ray flux-limited surveys suffer from a detection bias towards binarity.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the numbers and sizes of far flung proplyds are consistent with statistical expectations based on the X-ray luminosity function (though the correlation between instantaneous X-ray luminosity and resolvable proplyd structure on a source by source basis is weak, an effect that might be attributed to variability). Similarly there are far flung proplyds detected in Carina (Smith et al 2003), NGC 3603 (Brandner et al 2000) and Cyg OB2 (Wright et al 2012) although some of these are likely to instead be ionised clumps of molecular gas (Sahai et al 2012 a,b).…”
Section: The Observational Evidence For External Photoevaporation In mentioning
confidence: 97%